Persepsi Guru Tentang Pembelajaran pada Kurikulum 2013 dan Kurikulum Tingkat Satuan Pendidikan di SD Muhammadiyah 24 Gajahan Surakarta - Arum, Anggita Setya, Drs. Saring Marsudi, SH. M.Pd (2017)
This study aimed to describe perception of teacher about Learning in Curriculum 2013 and School Based Curriculum in Muhammadiyah Elementary School 24 Of Gajahan Surakarta. his study used a qualitative approach with descriptive litative research design. The technique data collection using are observation, interviews, and documentation. The results showed that teacher's understanding about Curriculum 2013 and KTSP good because it has been able to explain the characteristics of both the curriculum, Muhammadiyah ementary School 24 Of Gajahan Surakarta already apply the learning to use the Curriculum 2013 and KTSP both in the planning of learning and evaluation of learning. But teachers still experience some problems when using both the curriculum, since both of these curricula have pros and cons. Among both the curriculum more teachers who choose the Curriculum in 2013 for use in the learning process because Curriculum 2013 emphsis on yhe attitudes, knowledge and skills.